Comparing Lexical and Grammatical Development in Morphologicaly Different Languages - Kovačević, Melita (Array, 1998)
The purpose of this paper is to point to the variety of problems encountered in comparing the development of children acquiring morphologically diverse languages, with particular focus on the lexicon as well as verb and noun inflections (e.g. case and plural marking on nouns, past, imperative, person and number marking verbs). Examples are drawn from two Indo-European languages, Croatian and English which stand at opposite ends of the synthetic to analyitic scale. results from a Croatian parent/report study contrasted to those of an English one show that comparison gets more comlicated as significant structural specifities appear, particulary because of the differences in the richness of inflectional morphology which my affect the child`s lexicon.